Germline variants in UHRF1 are associated with multilocus imprinting disturbance in humans and mice - Eguzkine Ochoa; Ilona Zvetkova; Sunwoo Liv Lee; Nozomi Takahashi; Benoit Lan-Leung; Emma Hobson; Mahmoud Issa; Bryndis Yngvadottir; France Docquier; Fay Rodger; Dounia Foster-Hall; Graeme Clark; et al. (Proceedings of the National Academy of Sciences, 2025)
The investigation of congenital imprinting disorders (CIDs) provides opportunities to elucidate the molecular mechanisms and role of genomic imprinting in development and human disease. Beckwith–Wiedemann spectrum (BWSp) is a prototypic CID resulting from genetic and epigenetic alterations of imprinted genes at chromosome 11p15.5. In up to a quarter of individuals with BWSp, the epigenetic alterations are not confined to 11p15.5 imprinting control regions but also involve other imprinted gene clusters (multilocus imprinting disturbance; MLID). In a consanguineous family with two children diagnosed with BWSp and MLID, the affected individuals were homozygous for a missense variant in UHRF1 , a gene previously implicated in the maintenance of DNA methylation. To investigate whether the UHRF1 c. 2001G>C, p.(Lys667Asn) missense substitution predisposes to abnormal establishment/maintenance of genomic imprinting patterns, a genetically engineered mouse model with a Uhrf1 p.(Lys661Asn) variant was developed. Mice homozygous for the variant born to heterozygous mothers did not display an abnormal phenotype, but homozygotes born to healthy homozygous mothers displayed a range of phenotypes including prenatal lethality. Also, MLID was observed in affected mouse embryos. These findings are consistent with biallelic UHRF1 variants in affected individuals resulting in an autosomal recessively inherited cause of MLID in humans and expand the range of epigenetic disorders associated with UHRF1.